By-pass sediment system to replace longshore current in harbour areas - Cianflone, Giuseppe; Imbrogno, Gianpietro; Nguebiapssi Kembeu, Flaubert; Penna, Nadia; Domenico Ferraro; Daniele Cirillo; Ietto, Fabio; Dominici, Rocco (Italian journal of engineering geology and environment, 2024)
This paper is part of the results achieved in Tech4You project T4Y S2G2PP2 funded by PNRR (Piano Nazionale di Ricerca e Resilienza). The Tech4You project focused on the silting process affecting the Cetraro harbour mouth (Calabria, southern Italy). The study area is located along the northern Calabrian Tyrrhenian coast and is part of a physiographic unit with a west-southwest fetch greater than 1650 km. The wave climate is characterised by a significant wave height of 0.65m (average period of 5.15s) and 1.01 m (average period of 5.7s) offshore and inshore, respectively. The longshore flow of sediments (about 80,000 m3/yr), moving from north to south, is interrupted by the harbour pier producing silting ( 10,000 m3/yr sediment deposited at the harbour mouth), and heavy coastal erosion in the down-drift sector. The sediment production in the Aron River catchment (representing the main sediment feed in the physiographic unit) by Gravrilovic model was also studied, with detailed analysis of soil use through multispectral analysis, and estimate an average volume of 30,000 m3/yr. A bypass system was designed, consisting of a submerged pump installed at the end of the pier on the up-drift side of the harbour, to replace the original longshore current, contrasting simultaneously both mouth silting and erosion processes in the down-drift coastline.